PSYCHOLOGICAL AND PEDAGOGICAL CHARACTERISTICS OF CHILDREN’S PHYSICAL AND MENTAL DEVELOPMENT IN RULED GAMES - Umarova, Mekhriniso Ibragim qizi (Educational Research in Universal Sciences, 2023)
The game not only improves cognitive processes, but also positively affects the behavior of the child. This article discusses the psychological problems associated with the formation of behavioral skills in preschoolers, and also mentions the types of games and the fact that behavioral skills are easier and earlier acquired in the game than in purposeful activities.